Validating the Psychosocial Functioning during COVID-19 Questionnaire among a Sample of Informal Caregivers. (February 2021) - Arnold, Trisha; Kunicki, Zachary J.; Rogers, Brooke G.; Haubrick, Kayla K.; Klasko-Foster, Lynne; Norris, Alyssa L.; Drohan, Megan M.; Greaney, Mary L.; Cohen, Steven A.
The COVID-19 pandemic has had a dramatic impact on global economies and societies. Although social distancing policies are needed to contain the spread and impact of COVID-19, they also impose a psychological and economic burden on people who are already experiencing increased distress such as caregivers. Yet, few measures have been developed and validated to measure the psychosocial impact of COVID-19. Utilizing item response theory (IRT), the purpose of this study was to develop and psychometrically validate a measure of psychosocial functioning—the Psychosocial Functioning during COVID-19 (PFC-19) Questionnaire—to assess changes in social interaction, mental health, health behavior, and global functioning among a sample of informal caregivers during the COVID-19 pandemic. The analytic sample ( n = 733) was recruited from Amazon Mechanic Turk (MTurk) (69% male, 55% white). Results suggest a two-factor measure, assessing global functioning (14 items) and affective response (8 items), with strong evidence for reliability, validity, and dimensionality. Future research should replicate this factor structure in other samples.